(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
In this paper, the investigator studied the honors of Dr. A.P.J. Abdul Kalam served as president of the Republic of India from 2002 to 2007. He was a recipient of several prestigious awards, including the Bharat Ratna. There is a statue of Kalam in the entrance showing him playing the Veena. There are two other smaller statues of the leader in sitting and standing posture. The filter on which the new bug was found remained onboard the ISS for 40 months. Called a high-efficiency particulate arrestance filter or HEPA filter, this part is the routine housekeeping and cleaning system onboard the international space station. There are two other smaller statues of the leader in sitting and standing posture. They will get six options instead of three now, he said. The planetarium witnessed a footfall of 2,53,268, including 1,00,407 children while the science and evolution park registered 3,99,328 visitors in the past one year. Now it is in its newly inaugurated campus in Janki Puram, Lucknow LKO. Additionally, the university had a Centre and Regional Office in Noida, Uttar Pradesh, which was retained by Mahamaya Technical University.